PENGARUH SERAPAN SINAR MATAHARI OLEH KACA FILM TERHADAP DAYA KELUARAN PLAT SEL SURYA - Ricko Mahindra; Awitdrus '; Usman Malik (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This research is to determine the absorption of solar radiation by solar module which layered by polyester window films with the darkness of 40, 60, and 80% of the output power from the polycrystalline silicon solar module. It is then compared with the standard module. The current and voltage data of solar module are recorded by using Solar Charger Controller Model VS2024N every 1 hour from 10:00 am to 17:00 pm during 3 days. The solar module power output decreased with increasing the time. The power output of solar modules layered by window film influences significantly from 23.53% until 24.39%. The maximum output power is obtained from the window film darkness with level of 60%.